2014
DOI: 10.1093/carcin/bgu183
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 regulates epithelial-mesenchymal transition (EMT) in prostate tumorigenesis

Abstract: Poly (ADP-ribose) polymerase (PARP) is involved in key cellular processes such as DNA replication and repair, gene transcription, cell proliferation and apoptosis. The role of PARP-1 in prostate cancer development and progression is not fully understood. The present study investigated the function of PARP-1 in prostate growth and tumorigenesis in vivo. Functional inactivation of PARP-1 by gene-targeted deletion led to a significant reduction in the prostate gland size in young PARP-1-/- mice (6 weeks) compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 50 publications
2
48
0
Order By: Relevance
“…Of note, the role of PARP-1 in fibrosis may differ depending on the affected organ systems. In internal organs such as liver, lungs and kidneys, most publications report that PARP-1 promotes epithelial-to-mesenchymal transition (EMT) and fibrosis,34–38 while other studies report exacerbation of EMT by inhibition of PARP-1 39. Consistent with the different outcomes in fibrosis, inhibitory as well as stimulatory effects of PARP-1 on TGFβ/Smad signalling have been reported in vitro 15 16 37 39–41.…”
Section: Discussionmentioning
confidence: 97%
“…Of note, the role of PARP-1 in fibrosis may differ depending on the affected organ systems. In internal organs such as liver, lungs and kidneys, most publications report that PARP-1 promotes epithelial-to-mesenchymal transition (EMT) and fibrosis,34–38 while other studies report exacerbation of EMT by inhibition of PARP-1 39. Consistent with the different outcomes in fibrosis, inhibitory as well as stimulatory effects of PARP-1 on TGFβ/Smad signalling have been reported in vitro 15 16 37 39–41.…”
Section: Discussionmentioning
confidence: 97%
“…68 Acquisition of the mesenchymal phenotype is functionally associated with the ability to overcome anoikis. 69 Growing evidence links EMT induction to apoptosis evasion via upregulation of Bcl-2 antiapoptotic proteins and/or activation of the PI3-K/Akt prosurvival pathways, often associated with the downregulation of proapoptotic proteins such as Bim, Bax, Noxa, p21, and p53 effector related to pmp22Y. 7072 …”
Section: Emt Landscape In Control Of Cell Fatementioning
confidence: 99%
“…11.6) [25]. In BxPC-3 cells, no significant change in Snail expression was observed after exposure to TGF-β1 or hyperthermia; this caused us to investigate ZEB-1 expression in BxPC-3 cells [26][27][28]. We observed that ZEB-1 expression was upregulated by TGF-β1 treatment in BxPC-3 cells; this upregulation was then significantly blocked by hyperthermia ( Fig.…”
Section: Hyperthermia Inhibits Tgf-β-induced Emt In Pancreatic Cancermentioning
confidence: 90%